Recent progress in stretchable and self-healable supercapacitors: active materials, mechanism, and device construction. (1st July 2022) - Tung, Yen-Yu; Gull, Sanna; Ni, Chung-Sheng; Chiu, Wan-Ju; Chen, Han-Yi
Abstract: With the increasing popularity of wearable electronics and flexible screens in recent years, stretchable supercapacitors (SCs) have gained immense attention. However, such devices are often operated under conditions that cause large-scale deformation. Therefore, the self-healing of these devices during damage is also gradually being considered. This review introduces the recent research on stretchable and self-healing SCs and the effects of device construction, current collectors, and electrolytes on their mechanical stretchability, electrochemical performance, and practical applications. Finally, the limitations in the practical applications of such SCs and the possible solutions are discussed to provide an understanding for the development of high-performance devices in the future.